Investigation of Solvent-Dependent Catalytic Behaviour of Hydrophobic Guest Artificial Glutathione Peroxidase - Yin, Y.Z.; Wei, Y.; Shi, Z.F.; Shi, H.X.; Hu, X.X.; Jiao, S.F.; Chen, D.H. (Asian Journal of Chemistry, 2014)
To reveal the relation between the catalytic rate of artificial glutathione peroxidase (GPx) and the property of solvent used in the determination of catalytic behaviour of glutathione peroxidase (ADA-Te-ADA) was investigated. Ethanol, DMSO, DMF and CH3CN were selected as the co-solvent in the determination of catalytic rates. It was proved that ADA-Te-ADA exhibited the typical solvent-dependent catalytic behaviour. Moreover, compared with other co-solvents, the higher catalytic rate was observed when polar protic solvent (ethanol) was used. It suggested that the polar protic solvent was the appropriate co-solvent for the catalytic activity assay of hydrophobic artificial glutathione peroxidase. The strong polarity of polar aprotic solvent played an important role in the enhancement of glutathione peroxidase catalytic activity. This study explains the understanding of the catalytic behavior of hydrophobic guest artificial glutathione peroxidase when co-solvent was used.